The Influence of Leadership and Work Discipline on Employee Performance: Study at a Beauty Clinic in Bandung - Erina Anggraena; Ujang Wawan Sam Adinata; Adang Adang; Djadjun Djuhara; R. Rahadian Arby (Majalah Bisnis & IPTEK, 2024)
This study seeks to assess the impact of leadership and work discipline on employee performance in a beauty clinic in Bandung. The variables employed are X1 = Leadership, X2 = Work Discipline, and Y = Employee Performance. The data comprises questionnaire responses collected from employees of a beauty clinic in Bandung. A descriptive verification research method elucidates the link and influence among variables. This research employed a case study methodology for statistical testing, utilizing correlation analysis, path analysis, and the coefficient of determination. The data analysis indicates a correlation coefficient of 0.672, signifying a strong association between leadership and work discipline. Path analysis indicates the equation Y = 0.394X1 + 0.526X2, wherein leadership (X1) exerts an impact of 0.349 on employee performance, while work discipline (X2) exerts an influence of 0.526. The coefficient of determination is 0.711, indicating that leadership and work discipline account for 71.1% of employee performance at a beauty clinic in Bandung. In comparison, the remaining 28.9% is attributed to other unexamined factors.